Die Vollstreckungsimmunität der Staaten im Wandel des Völkerrechts = State immunity from measures of contraint in a changing public international law (English summary) /: State immunity from measures of contraint in a changing public international law (English summary). ([2018]) - Höfelmeier, Anja
No abstract available